Congenital or acquired? A case report of extensive congenital cholesteatoma - Roslenda AR,; Asma A,; Iqbal FRW,; Iqbal FRW, (Penerbit UKM, 2010)
Congenital cholesteatoma (CC) is rare clinical condition and It is known as a pearly white mass medial to an intact tympanic membrane. In this case report, we describe a 6-year-old boy who presented with a one year history of left ear discomfort, reduced hearing, followed by ear discharge two months prior to admission. Otoscopic examination revealed a large attic perforation. Radiological investigation showed extensive cholesteatoma in the mastoid, mesotympanum and epitympanum with destruction of the ossicles including the stapes footplate. He underwent radical mastoidectomy in view of extensive cholesteatoma with tympanoplasty type V. In this case report, the classification, treatment and theories related to CC are discussed.